Stalking and cyberstalking in college students: A systematic review - Pires, Sara A. (2018)
Objectives: This article aims to contribute to the knowledge of the phenomena of stalking and cyberstalking through the identification and analysis of the empirical studies concerning the occurrence of phenomena in university students. Methods: We adopted the procedures for a systematic review of the research carried out on the occurrence of stalking and cyberstalking in university students. Results: The results showed the predominance of cross-sectional studies and using exploratory, correlational, and descriptive designs focused on the victim. The most common instruments used in order to evaluate both phenomena are diverse, but all studies used self-reporting inventories. The prevalence of stalking and cyberstalking reported was very different (e.g., 12% e 96% throughout life). Further analysing of stalking and cyberstalking and the respective human dynamics and behaviour, indicate that the common victims were identified as female gender. The offenders were mostly characterized as males, and these phenomena commonly derive from an intimate relationship or interaction with other individuals on a daily basis (e.g., class colleague, family member or neighbour). The occurrence of stalking and cyberstalking affect mostly psychological and physical health and also consequences to the students’ lifestyle and economic state. As for the answers of victimization, the most recurred sources of support were of the informal type. Conclusions: Relatively to stalking or cyberstalking phenomena in college students, we conclude that there is a predominance of prevalence and cross-sectional studies, using different types of instruments. We believe that the research may cover other samples, continuity studies, benefiting from a uniform selection of instruments for data collection and the study of the co-occurrence of phenomena.